Peran FIFA Dalam Upaya Penyelesaian Konflik Dualisme PSSI di Indonesia Pada Tahun 2011-2013 - Wima Putra, I Putu Wintara; Priadarsini, Ni Wayan Rainy; Resen, Putu Titah Kawitri (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
Football, which is the most popular sport in the world, has the highest authority organization named FIFA. FIFA has the authority to make every rules and regulations about football that must be obeyed by every members of FIFA. FIFA consist of every main football organizations all over the world, including Indonesia which has a main football organization called PSSI. In Indonesia, football is also one of the most popular sport among public, Indonesia also known as a country with huge fanaticism supporters. Having massive fans now made football a promising business. On the other side, with too many interested parties made this business susceptible of conflicts among those interested parties. In Indonesia for example, the issue about football was starting when FIFA thought that at Nurdin Halid leadership era PSSI lose its credibility and then there were also the time when dualism in PSSI occurred where there were two leaders inside PSSI, one led by Djohar Arifin and the other led by La Nyalla Mattalitti under the name of KPSI. This duality problem occurred because of the difference of opinion about Indonesia’s main league. This chaos made FIFA went directly to resolve the conflict in PSSI. As International organization, FIFA can do its role and function well, so that through a long process FIFA can reunite PSSI. Keyword : FIFA’s Role, Football. International Organization, PSSI Dualism.